THE IMPLEMENTATION OF RECIPROCAL TEACHING IN READING CLASS - Irene Trisiska M.Pd.; Maria G. Sri Ningsih (JURNAL ILMIAH BAHASA DAN SASTRA, 2019)
This research was conducted to find out how the application of reciprocal teaching can improve student’s understanding in reading subject. The application of Reciprocal Teaching can help university students as prospective educators to be able to improve their creativity. This research used Classroom Action Research (CAR) which had four steps of research procedures namely planning, implementing, observing, and analyzing. The subjects of this study were fourth semester students of Kanjuruhan University of Malang who took critical reading course. To achieve the criteria for success, researchers took two cycles by adopting theories from Kemmis and Taggart. In the first cycle, students who achieved success criteria were 43.47%. However, the success criteria targeted by researchers were75%. In the second cycle the success rate of students reached 82.60%. The conclusion of this study is that teaching reading using reciprocal can increase student motivation and increase student interaction. Because interaction with other students and with lecturer increases, motivation to learn and confidence also increases, it can also improve student learning outcomes. Positive competitiveness is also shown by students bravely expressing their ideas quickly. The application of reciprocal teaching in the class has problems including controlling classroom situations, there are some students who rely on their friends in doing work, and there are some students who are a bit selfish and feel that working together in working on problems makes them slow because they have to explain their opinions and then put forward in front of the class.